The Mediating Role of Perceived Efficacy in the Relationship of Climate Anxiety and Pro-Environmental Behaviors among Young Adult Filipinos - Corina Myers; Andrew Macalma (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2025)
The Philippines is vulnerable to environmental impacts, from the destruction of homes, disruption of livelihoods, displacements, and death, prompting more studies of its effects in Environmental psychology. The study’s results are important in understanding the involvement of the relationship among climate anxiety, pro-environmental behaviors, perceived self-efficacy, and perceived collective efficacy among individuals who are most impacted by climate change. This study explores the mediating role of Perceived Efficacy in the relationship between climate anxiety and pro-environmental behaviors of 312 Filipinos aged 18 to 30 through an online survey. A positive correlation was found between climate anxiety and pro-environmental behaviors in both private and public spheres. In the mediation analysis, higher anxiety resulted in results of increased perceived efficacy, showing an increased involvement in pro-environmental behaviors among young adult Filipinos. This highlights the significance of perceived efficacy in promoting environmental actions among young adult Filipinos, suggesting an understanding of possible measures to alleviate the effects of climate change for young adult Filipinos affected by the health impacts and climate-related fatalities.